Two new species of Tetrathylacium (Salicaceae) from Ecuador - Santamaría-Aguilar, Daniel; Liesner, Ronald L.; Monro, Alexandre K. (Phytotaxa, 2019)
Two new species from Pastaza Province Ecuador, Tetrathylacium longirachis and T. sarayakuorum are described and illustrated, one species name previously placed in synonymy, T. nutans is recognized as a distinct species and illustrated. In doing so we increase the number of accepted species in the genus from two to five and identify the Pastaza region in Ecuador as an area of exceptional species richness for Tetrathylacium. We also lectotypify the generotype, T. macrophyllum and neotipify T. nutans. In addition, we provide a key for the identification of the species.